Effect of Air Velocity on the Performance of CO2 Evaporator with Different Flow Numbers (Zhileng xuebao)
In order to study the relationship between air velocity and heat transfer performance of CO2 finned-tube evaporator, a distributed parameter model was established in this paper. The changes of refrigerant pressure drop, heat transfer, temperature distribution and heat transfer coefficient of five kinds of flow-number were analyzed under conditions of evaporation temperature of -25 ℃ and air velocity of 0.5~4 m/s, and the reliability of the model was experimentally verified. Compared with the experimental values under the same working conditions, the relative error of the simulation model for predicting the heat transfer, refrigerant pressure drop and air side pressure drop was less than ±4%. Simulations demonstrated the heat transfer, refrigerant pressure drop and heat transfer coefficient of the evaporator with the same flow number all increase with the increase of air velocity, while the increase range decreases with the increase of air velocity. The optimal air velocity range is 2.5~3.5 m/s, reflecting the heat transfer effect and energy consumption. Choosing more flow numbers in a reasonable range can effectively improve the heat transfer performance and enhance the heat transfer uniformity in evaporator design. In this experiment, the 24 flow number evaporator is the best design scheme.